Effectiveness of used engine oil on improvement of properties of fresh and hardened concrete - Shafiq, Nasir; Nuruddin, Muhd. Fadhil; Kamaruddin, Ibrahim (2006)
Use of mineral admixtures, processed and unprocessed industrial by-products and domestic and agricultural wastes as raw materials in cement and concrete is becoming popular. This has a positive environmental effect as the cost of safe disposal of waste is significantly higher and there are strict environmental regulations. Some references indicate that the leakage of oil into the cement in older grinding units resulted in concrete with greater resistance to freezing and thawing. This effect is similar to adding an air-entraining chemical admixture to the concrete. However, the hypothesis is not backed by significant research study reported in the available literature. This research study was conducted to investigate the effects of used engine oil on properties of fresh and hardened concrete. The main variables included the type and dosage of an airentraining agent (SIKA AER commercially available air entraining agent, used engine oil, and new engine oil). Results showed that used engine oil increased the slump between 18 to 38% and air content between 26 to 58% with respect to the control mix containing no admixture, used engine oil reasonably reduced the porosity and did not adversely affect the strength properties of hardened concrete.